Pendampingan dan Pengembangan Manajemen Pemasaran Produk UMKM Tanaman Hias Melalui Teknologi Digital di Masa Pandemi Covid-19 - Umarudin, Muhammad; Jalaludin, Jalaludin; Winny Arditta, Thasya (STIE Syariah Indonesia Purwakarta, 2022)
Micro, Small and Medium Enterprises (MSMEs) often face various challenges, but this is not an obstacle for MSMEs to develop and become even more advanced. Digital flows are increasingly swift, making old MSMEs who lack technology education left behind and buried by competitors who are already literate in technology. The purpose of this Community Service Program (PKM) is to assist ornamental plant MSMEs in conducting digital marketing and to assist partners to find solutions to problems encountered in an effort to develop their business. This PKM method uses an approach of observation, preparation, socialization and evaluation. The results of this PKM were very welcomed by ornamental plant MSME actors, because for these ornamental plant MSME actors they are no longer young, technology is an obstacle to their business, due to lack of knowledge of technology their businesses are left far behind in developing. During the mentoring and development of online or digital marketing management, there have been many changes starting in terms of promotions which usually only rely on neighbors who buy, now they are using Instagram, apart from that, ornamental plant MSMEs can also arrange flower displays so that they look attractive when they are at home. Upload to social or digital media. Several orders came in from outside the sub-district and city with this PKM program. Other supporting activities include outreach to MSME Bonsai Gardens and Wedding Organizers. The PKM team program was welcomed by MSME players. On the other hand, it is to add to their knowledge base, on the other hand, it is also a means of expanding marketing networks.